2008
DOI: 10.1158/1078-0432.ccr-07-0867
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Restricted Replicative Adenovirus Expressing Human Endostatin-Angiostatin Fusion Gene Exhibiting Dramatic Antitumor Efficacy

Abstract: Purpose: Our previous studies coadministering a replication-deficient adenovirus expressing endostatin and angiostatin fusion gene (EndoAngio) and a prostate-restricted, replicationcompetent adenovirus (PRRA) showed dramatic antitumor efficacy. This study integrated EndoAngio with an improved PRRA vector to make a single antiangiogenic PRRA, thereby exerting a similarly dramatic antitumor effect with feasibility for future clinical trials. Experimental Design: We developed an antiangiogenic PRRA with structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…35 Although the antitumor effects are temporary and subpar to completely lead to tumor regression, this is not uncommon as antiangiogenesis monotherapy fails to block tumor progression in the clinical studies. 36 Nevertheless, antiangiogenic agents can make the tumor more susceptible to eradication, enhancing the effectiveness of radiotherapy or chemotherapy, even at lower cumulative doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Although the antitumor effects are temporary and subpar to completely lead to tumor regression, this is not uncommon as antiangiogenesis monotherapy fails to block tumor progression in the clinical studies. 36 Nevertheless, antiangiogenic agents can make the tumor more susceptible to eradication, enhancing the effectiveness of radiotherapy or chemotherapy, even at lower cumulative doses.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Bac-ITR-hEA may be administered intramuscularly because muscle provides a microenvironment more suitable for sustained expression and hEA can exert the antitumor effects via systemic administration. 4 Finally, although hEA gene delivery can be achieved by either adenovirus 35 or vaccinia virus, 8 the pre-existing immunity against these vectors in humans can attenuate the antitumor efficacies. In contrast, baculovirus is an insect virus in nature, and humans do not appear to possess preexisting antibody and T cells specifically against baculovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin, a 20-kDa C-terminal fragment of collagen XVIII, is the most potent angiogenesis inhibitor and specifically inhibits endothelial cell proliferation and migration, induces apoptosis of vascular endothelial cells (Lai et al, 2007;Li et al, 2008;Ning et al, 2008), and has been demonstrated to be with antitumor effect in many solid tumors, and without toxicity, immunogenesis or resistance. The adenovirus vector carrying a secretable form of mouse endostatin, Av3mEndo, mediated the secreted expression of endostatin from Av3mEndo-transduced mammalian cells and showed a potential inhibition of endothelial cell migration in vitro.…”
Section: Crad With Antiangiogenesis Genementioning
confidence: 99%
“…351 Li et al's recent study indicated that a replication-deficient adenovirus expressing endostatin and angiostatin fusion gene (EndoAngio) and a prostate-restricted, replication competent adenovirus (PRRA) showed dramatic antitumor efficacy. 352 EndoAngio-PRRA uniquely combines three distinct antitumor effects to eliminate AI CaP: anti-angiogenesis, viral oncolysis, and apoptosis. 352 This novel anti-angiogenic PRRA represents a powerful agent feasible for future clinical trials for CaP therapy.…”
Section: Endogenous Angiogenesis Inhibitorsmentioning
confidence: 99%